A RARE CASE OF CLITORAL NEUROFIBROMA - Hafiz Nurdiansyah; Henny Maisara Sipahutar (PT. Radja Intercontinental Publishing, 2023)
Cltoral neurofibromas are benign tumors originating from peripheral nerves of the clitoris. While neurofibromas can occur in various anatomical locations, their occurrence in the clitoral region is extremely uncommon. Few cases of clitoral neurofibromas have been reported in the literature, and even fewer have focused on the radiologic imaging findings. Therefore, there is a limited understanding of the specific radiologic characteristics of clitoral neurofibromas. We present a 38-year-old woman with painless clitoral mass for the previous 2 years. The patient noted the mass to be enlarged in the past 5 months. Physical examination revealed a palpable and well-circumscribed mass arising from the clitoral shaft. Cytological examination was performed with the impression of fibroma. Contrast enhanced CT scan revealed an ovoid, well-circumscribed enhancing mass on clitoris shaft suggestive of a benign lesion, consistent with description provided. Surgical excision biopsy was performed followed with histopathological examination with the impression of neurofibroma.This case report considered highly specific examination for the clitoral neurofibroma.